Filsafat Stoisisme dalam Perspektif Etika Kristen - Remegises Danial Yohanis Pandie (Sekolah Tinggi Teologi Real Batam, 2023)
The philosophy of Stoicism plays an important role in human life. The role of Stoicism includes human ethics in responding to things that happen around him such as situations that disturb human psychology. Stoicism is not just a theory, but a set of practices designed to help humans live better lives. Stoicism proposes a code of masculinity based on extraordinary mental strength. Stoicism teaches people how to maintain peace of mind from the sensitivity of circumstances. Stoicism sees human psychological problems as the product of misjudgment and can be eradicated with a form of cognitive psychotherapy. In practice, there are still many people who do not understand and have not really practiced the philosophy of Stoicism under the pretext of not being in accordance with the teachings of Christianity. The purpose of this research is to examine the parts of Stoicism and their relation to Christian ethics. The research method used is descriptive qualitative. The result of the research is that there is a belief that what Christ revealed, is a rational principle explored by Stoicism, so reason and revelation must complement each other. The main point in determining or verifying the life of each individual must be through biblical standards.Keywords: christian ethics; philosophy; stoicism AbstrakFilsafat Stoisisme memainkan peran penting dalam kehidupan manusia. Peranan Stoisisme mencakup etika manusia dalam menyikapi hal-hal yang terjadi disekitarnya seperti situasi-situasi yang mengganggu psikologis manusia. Stoisisme bukan hanya teori, tetapi seperangkat praktik yang dirancang untuk membantu manusia menjalani kehidupan yang lebih baik. Stoisisme mengusulkan kode maskulinitas berdasarkan kekuatan mental yang luar biasa. Stoisisme mengajarkan manusia bagaimana menjaga ketenangan pikiran dari sensitifitas keadaan. Stoisisme melihat masalah psikologis manusia sebagai produk dari penilaian yang salah dan dapat diberantas dengan suatu bentuk psikoterapi kognitif. Dalam praktiknya, masih banyak orang yang belum memahami dan belum benar-benar menjalankan filosofi Stoisisme dengan dalih tidak sesuai ajaran agama Kristen. Tujuan penulisan ini adalah mengkaji bagian-bagian Stoisisme dan kaitannya dengan etika Kristen. Adapun metode penelitian yang digunakan adalah kualitatif deskriptif. Hasil penelitian yaitu ada keyakinan bahwa apa yang diwahyukan Kristus, adalah prinsip rasional yang dieksplorasi oleh Stoisisme, sehingga akal dan wahyu harus saling melengkap. Titik utama dalam menentukan atau verifikasi kehidupan setiap individu harus melalui standar Alkitab.Kata kunci: etika kristen; filsafat; stoisisme